NUANCES OF CHARACTER DISPOSITION REPRESENTING THEMES OF LOSS AND RECOVERY IN ANNE OF GREEN GABLES AND THE SECRET GARDEN - Luntungan, Jacqueline Candace; Sigarlaki, Stephani Johana; Marentek, Andriyani (Journal of English Language and Literature Teaching, 2024)
The Nuances of Character Disposition in Representing Themes of Loss and Recovery has the objectives of: (1) to identify and describe the nuances of character disposition in representing themes of loss and recovery as depicted in Anne of Green Gables by Montgomery (1908) and The Secret Garden by Burnett (1911); (2) to analyse and compare the nuances of character disposition in representing themes of loss and recovery as depicted in Anne of Green Gables by Montgomery (1908) and The Secret Garden by Burnett (1911). By utilising the theory of theme, the tripartite model deriving from the psychoanalytical theory, character theory and bildungsroman, it was intrinsically and extrinsically explained in regards to the representation of themes. Certain psychoanalytically categorised behaviours exuded from the characters that affect their disposition towards the events they undergo throughout the story, also defines their similarities and contrasts. This study used the qualitative method, that focused on collecting and describing written data from the source material and interpretation. The results of this study show that the representations of loss and recovery are identified in both characters and their behaviours that were psychoanalytically categorised. Through this categorisation, Anne and Mary’s initial opposition in their dispositions gradually began to alter their perception which allowed for comparisons to be drawn for their similarities and differences.